Immediate implant-based breast reconstruction using the TIGR® Matrix mesh. (May 2016) - Schrenk, Peter
Background: Different types of acellular dermal, synthetic and biological matrices have been used in connection with immediate implant-based breast reconstruction.Patients & methods: A new long-term absorbable surgical matrix, TIGR® Matrix mesh was used in a total of 29 patients undergoing a total of 37 mastectomies and immediate reconstruction.Results: Early postoperative results showed no adverse reactions to the mesh and a good integration into the tissue.Conclusion: It may therefore constitute an alternative to acellular, dermal or other synthetic matrices currently available.